A novel architecture of an optical cross-connect based on tuneable fibre bragg gratings and optical circulators - O. Frazão (2002)
Optical networks have evolved to sustain the growing need for bandwidth in communication networks. Wavelength switched networks using Dense WavelengthDivision Multiplexing (DWDM), are a solution to this problem. Development of these networks demands the use of Optical Cross-connects (OXCs), optical devices that are able to control the communications channels and route them correctly. In this paper, a novel switching architecture based on thermally tuneable Fibre Bragg Gratings (FBG) and optical circulators (OC) is demonstrated.